Historical dictionary of football - Grasso, John (Historical dictionaries of sports., 2013)
The Historical Dictionary of Football covers the history of American football through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 600 cross-referenced entries on both amateur (collegiate) and professional players, coaches, teams and executives from all eras. This book is an excellent access point for students, researchers, and anyone wanting to know more about the sport of football.